2001
DOI: 10.1159/000049283
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Multiaxial System of ICD-10 (Preliminary Draft): Correlations between Multiaxial Assessment and Clinical Judgements of Aetiology, Treatment Indication and Prognosis

Abstract: Forty-five raters in 7 German centres took part in a multicentric field trial of the multiaxial system of ICD-10, delivering a total of 488 multiaxial assessments of 12 written case summaries. In addition to the multi-axial ratings (including main and subsidiary psychiatry diagnoses, level of social dysfunctioning and psychosocial stressors), assessments were made by the raters of the aetiology, treatment indications and prognosis of the main psychiatric disorder. There were significant correlations between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
1
7
0
1
Order By: Relevance
“…These values correspond approximately to the results of an earlier OPD practicability study by Michels et al [44] , which was also conducted under the conditions of clinical routine.…”
Section: Reliability Measures (Axis I-iv)supporting
confidence: 88%
See 1 more Smart Citation
“…These values correspond approximately to the results of an earlier OPD practicability study by Michels et al [44] , which was also conducted under the conditions of clinical routine.…”
Section: Reliability Measures (Axis I-iv)supporting
confidence: 88%
“…Concerning the reliability in clinical routine, it should be noted that ICD-10 is also only moderately reliable in clinical day-to-day use [44] . …”
Section: Reliability Measures (Axis I-iv)mentioning
confidence: 99%
“…We were particularly attentive to the need to achieve a high level of reliability for this measure. Previous studies using GAF scores have reported mixed success in achieving adequate reliability, with some studies reporting high agreement (e.g., Edson, Lavori, Tracy, & Adler, 1997) and some reporting relatively low agreement (e.g., Michels, Siebel, Freyberger, Schonell, & Dilling, 2001). However, the primary factors that appeared to promote reliability in GAF ratings across studies were that raters received training and were provided with sufficient clinical data to assess functioning (Jones et al, 1995).…”
Section: Studymentioning
confidence: 99%
“…The exploration of comprehensive diagnostic schemas for the development of future diagnostic systems shall require the empirical appraisal of the reliability and validity of the structure and components involved. A useful illustration is a recent evaluation by Michels et al [24] of the ICD-10 multiaxial system in consideration of the relevance of comprehensive diagnostic schemas to a care process focused on promoting the patient's health and quality of life in an ethical and culturally informed manner.…”
Section: Discussionmentioning
confidence: 99%